B-11 NMR-STUDIES OF AN ARYL BORONIC ACID BOUND TO CHYMOTRYPSIN AND SUBTILISIN - Baldwin, J; Claridge, T; Derome, A; Schofield, C; Smith, B (1991)
The binding of aryl boronic acids to α-chymotrypsin and subtilisin has been studied by 11B NMR spectroscopy; evidence is provided for the direct spectroscopic observation of a tetrahedral enzyme/boromate complex. © 1991.